Umphred's neurological rehabilitation - Umphred, Darcy Ann (Elsevier/Mosby, 2013)
Covers the therapeutic management of people with functional movement limitations and quality of life issues following a neurological event. This title reviews basic theory and covers the screening and diagnostic tests, treatments, and interventions commonly used in clinical practice. It includes advances in neuroscience.